Pedagogical Development of the Remo Bapang Jatiduwur Dance for Instructional Use at Sanggar Tri Purwo Budoyo - Biantoro, Aditya Putra; Yanuartuti, Setyo; Rahayu, Eko Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The Bapang dance within the Wayang Topeng Jatiduwur tradition in Jombang has experienced a significant decline due to a lack of regeneration, rendering it dormant for years. This study addresses the urgent need for choreographic reconstruction and development of the Remo Bapang Jatiduwur dance as a creative effort to preserve and reintroduce it to contemporary audiences. The objectives are twofold: (1) to describe the choreographic development process of Remo Bapang Jatiduwur as instructional material at Sanggar Tri Purwo Budoyo, and (2) to evaluate its feasibility for pedagogical implementation. The research is grounded in two theoretical frameworks: artistic reconstruction and choreographic development, combined with the concept of studio-based teaching materials. Methodologically, it integrates the Four-D development model (Define, Design, Develop, Disseminate) by Thiagarajan and Hawkins art creation process (exploration, improvisation, and forming). The findings reveal the creation of two choreographic works: a reconstructed version that revives traditional nuances, and a contemporary adaptation designed for educational relevance and inclusivity. Validation by experts and field testing at the studio showed strong cultural resonance, technical feasibility, and learner engagement. This study concludes that the developed choreography is viable for instructional use and contributes meaningfully to the revitalization of local performing arts, providing a sustainable model for heritage-based dance education.